Food Production and Domestication Produced Both Cooperative and Competitive Social Dynamics in Eastern North America. (4th July 2022) - Weitzel, Elic M.; Codding, Brian F.; Carmody, Stephen B.; Zeanah, David W.
ABSTRACT: Recent research emphasises the importance of both within-group cooperation and between-group competition for human sociality, past and present. We hypothesise that the shift from foraging to food production in eastern North America provided novel socioecological conditions that impacted interpersonal and intergroup interactions in the region, inspiring both greater cooperation as well as competition. We predict that (1) successful exploitation of this indigenous crop complex encouraged greater cooperation leading to site aggregation in high-quality locations as expected by an ideal free distribution with an Allee effect, and (2) continued population growth driven by the domestication and adoption of the crop complex eventually inspired a shift from positive to negative density dependent settlement dynamics, driving declines in site suitability. Our results demonstrate that there was an increase in both site clustering and site location quality coincident with crop management and domestication in the Middle Holocene, and that territorial violence appears at this time as well. Site quality later declined after c. 3000 cal BP, also as predicted. These results indicate that managing and domesticating plants inspired an Allee effect and led to greater within-group cooperation, but was also related to the rise of territorial between-group competition in the region.